2021
DOI: 10.1002/jts5.80
|View full text |Cite
|
Sign up to set email alerts
|

The role of collective narcissism in populist attitudes and the collapse of democracy in Hungary

Abstract: What are the psychological processes responsible for the recent spread of populist political systems and movements? All political systems essentially reflect the mental representations of their populations, and collective narcissism has recently emerged as a contributing factor in the rise of populism. This article presents two studies examining the role of collective narcissism in predicting populist attitudes and voting intentions in Hungary. Hungary offers a particularly important case study of state‐sponso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Surprisingly, this positive association was also found, albeit marginally weaker, among members of the disadvantaged group. This suggests that, even among disadvantaged groups, collective narcissism may be linked to conservative and hierarchy‐enhancing ideologies (Golec de Zavala et al., 2009; Lantos & Forgas, 2021). Furthermore, although the interaction patterns were consistent with other studies regarding support for BLM, the simple effects differed.…”
Section: Studymentioning
confidence: 99%
“…Surprisingly, this positive association was also found, albeit marginally weaker, among members of the disadvantaged group. This suggests that, even among disadvantaged groups, collective narcissism may be linked to conservative and hierarchy‐enhancing ideologies (Golec de Zavala et al., 2009; Lantos & Forgas, 2021). Furthermore, although the interaction patterns were consistent with other studies regarding support for BLM, the simple effects differed.…”
Section: Studymentioning
confidence: 99%
“…Although it can be speculated that the rise of national populism has been associated with an increase in the use of rhetoric that calls for a greater recognition of the exceptionalism of one's nation, we also did not find evidence for citizens' national narcissism to be higher in countries governed by populist leaders, regardless of the specific flavor of populism. However, this does not contradict research showing that individual levels of national narcissism might predict populism support within each country (e.g., Lantos & Forgas, 2021;Marchlewska et al, 2018). Additional factors beyond average societal levels of national narcissism, such as the nature of the political system, will determine whether populists actually assume power (Kyle & Glutchin, 2018).…”
Section: Discussionmentioning
confidence: 78%
“…The rise of national populism seems to be accompanied by a rhetoric that demands greater recognition of the exceptionalism of one's nation, and indeed past work has shown that national narcissism predicts support for populist leaders and politicians (Marchlewska et al, 2018). In the US, it was associated with support for Donald Trump , in Poland-with support for the ultra-conservative Law and Justice Party (Marchlewska et GLOBALIZATION AND NATIONAL NARCISSISM 10 al., 2018), and in Hungary-with support for the Fidesz party of Viktor Orbán (Lantos & Forgas, 2021). These effects are typically observed over and above factors such as partisanship and political ideology .…”
Section: Globalization Is Associated With Lower Levels Of National Na...mentioning
confidence: 99%
“…Indeed, populist rhetoric, defending a glorified nation against enemies, resonates with the national narcissistic beliefs (e.g., Golec de Zavala & Bierwiaczonek, 2021). Furthermore, the will to gain power (e.g., Cichocka & Cislak, 2020) and conservative values (e.g., Lantos & Forgas, 2021;Marinthe et al, 2022) are also strongly associated with national narcissists' beliefs. We thus argue that national narcissists (even outside of Russia) may perceive themselves as similar to Putin in terms of identity-related beliefs.…”
Section: National Narcissism and Support For Anti-democratic Outgroup...mentioning
confidence: 99%
“…This belief has consequences at the political level (Cichocka & Cislak, 2020), such as stronger support for populism and anti-democratic leaders and policies (Marchlewska et al, 2018). For example, people with higher levels of national narcissism in the US were more likely to support Donald Trump (Federico & Golec de Zavala, 2018), the populist ultraconservative Law and Order party in Poland (Marchlewska et al, 2018), Viktor Orbán's Fidesz populist party in Hungary (Lantos & Forgas, 2021) or to vote for Brexit in 4 Britain (Marchlewska et al, 2018). Populism can be defined as "an ideology that considers society to be ultimately separated into two homogeneous and antagonistic groups, 'the pure people' versus 'the corrupt elite', and which argues that politics should be an expression of the volonté générale (general will) of the people" (Mudde, 2004, p. 543).…”
Section: National Narcissism Populism and Anti-democratic Actionsmentioning
confidence: 99%